Le binome euro -dollar sous le signe de l’incertitude - Ana Bal (Romanian Journal of European Affairs)
Will the Dollar remain the dominant international currency (mainly as a reserve currency)? To answer this question, the paper presents in the first part the opinions of the most prominent experts concerning the determinant factors of an international currency status, in the two sphere of utilization: public and private. The most important are: the magnitude of the economies of emission, the externalities of network, the liquidity of their financial market, the confidence in their stability. Then there follows the evaluations concerning the two international currencies, Dollar and Euro, from these perspectives. Finally, the paper evaluates their role as measure of value, instrument of reserve and instrument of payment in the international economic relations. In the second part, the paper evaluates the recent tendencies of the exchange rate Euro/Dollar (2006-2008) from the point of view of fundamentals. After a period of depreciation, from the middle of the year 2008 until now, the dollar marked an unexpected appreciation towards the euro. But, the global financial and economic crisis increases the incertitude concerning the evolution of the exchange rate euro/dollar. Undoubtedly the two currencies will remain the prominent international currencies and the dollar the main reserve currency. Finally the paper presents Mundell’s proposal of stabilization of the binomial euro/dollar.